2018
DOI: 10.1016/j.applanim.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Less water renewal reduces effects on social aggression of the cichlid Pterophyllum scalare

Abstract: Changes in aquatic environments can affect fish behavior. Water renewal, for example, can dilute chemical signals, which are a social communication tool used by some fish species, and this dilution increases aggressive interactions in the group. Fierce and prolonged fights can affect fish welfare by increasing the probability of injuries, stress, and detrimental impacts on fish health. We tested whether the amount of water changed was associated with social aggression in the angelfish Pterophyllum scalare, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…In the juvenile angelfish cichlid, Pterophyllum scalare, for example, a change of 25% water stimulated aggressive interactions in the group for one hour, and after this period aggressive interactions returned to basal levels [12]. On the other hand, after changing 50% water, fish kept an increased aggressive interaction rate for 24 h [12]. Thus, it is possible that other cichlid species, such as Nile tilapia, also behave that way, although this hypothesis needs to be tested.…”
Section: Chemical Communication and Social Rank Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the juvenile angelfish cichlid, Pterophyllum scalare, for example, a change of 25% water stimulated aggressive interactions in the group for one hour, and after this period aggressive interactions returned to basal levels [12]. On the other hand, after changing 50% water, fish kept an increased aggressive interaction rate for 24 h [12]. Thus, it is possible that other cichlid species, such as Nile tilapia, also behave that way, although this hypothesis needs to be tested.…”
Section: Chemical Communication and Social Rank Signalingmentioning
confidence: 99%
“…When the external environment is changed, social communication can be impaired and social interactions can be affected. For instance, for some fish species chemical information is important in social rank communication [10], however, water dilution can dilute such information, thus, disturbing social stability and increasing aggressive interactions [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was most likely caused by the disruption of chemical communication due to changed water chemistry. Changing only a small volume of water at a time was in turn found to be a good solution to prevent exaggerated aggressive interactions in these fish, leading to a reduction of detrimental effects on fish welfare (Gauy, Boscolo, & Gonçalves‐de‐Freitas, ).…”
Section: Practical and Welfare Aspectsmentioning
confidence: 99%
“…Some differences in social signaling among them are expected, since the evolutionary mechanism favored differences in social behavior between these two large groups (Keenleyside, 1991;Barlow, 2000). In a recent study with juvenile Amazonian cichlid, Pterophyllum scalare (Schultze, 1823), Gauy et al (2018) found that chemical information is important to keep social stability within the group. For instance, the greater the renewal of aquarium water (and the more diluted chemical information), the greater the overt aggression in aggressive interactions, and longer time was needed to restore the baseline levels of aggression in the group.…”
Section: E180159[2]mentioning
confidence: 99%